Long-term Outcomes in a Large Randomized Trial of HIV-1 Salvage Therapy: 96-Week Results of AIDS Clinical Trials Group A5241 (OPTIONS). (28th May 2019) - Gandhi, Rajesh T; Tashima, Karen T; Smeaton, Laura M; Vu, Vincent; Ritz, Justin; Andrade, Adriana; Eron, Joseph J; Hogg, Evelyn; Fichtenbaum, Carl J
Abstract: Background: Short-term (48-week) results of the OPTIONS trial showed that nucleoside reverse transcriptase inhibitors (NRTIs) can be safely omitted from salvage therapy as long as the regimen has a cumulative activity of >2 active antiretroviral medications. The long-term durability of this approach and outcomes in persons who have more-extensive HIV-1 drug resistance are uncertain. Methods: Participants with virologic failure and anticipated antiretroviral susceptibility received an optimized regimen and were randomized to omit or add NRTIs. A separate group with more resistance (cumulative activity ≤2 active agents) received an optimized regimen including NRTIs. Results: At week 96, among 360 participants randomized to omit or add NRTIs, 70% and 65% had HIV-1 RNA <200 copies/mL, respectively. Virologic failure was uncommon after week 48. Younger age and starting fewer new antiretroviral medications were associated with higher odds of virologic failure. In the highly resistant group, 53% had HIV-1 RNA <200 copies/mL at week 96. Conclusions: HIV-1 salvage therapy can safely omit NRTIs without compromising efficacy or durability of response as long as the new regimen has a cumulative activity of >2 active drugs. Younger people and those receiving fewer new antiretrovirals require careful monitoring. Even among individuals with more-extensive resistance, most achieve virologic suppression. Clinical Trials Registration: NCT00537394. Abstract : HIV-1 salvage therapy can safely omit nucleoside reverse transcriptase inhibitors without compromising efficacy or durability of response as long as the new regimen has a cumulative activity of 2 or more active drugs.